COVID-19 and business failures: The paradoxes of experience, scale, and scope for theory and practice. Issue 2 (April 2021) - Amankwah-Amoah, Joseph; Khan, Zaheer; Wood, Geoffrey
Abstract: In light of growing scholarly works on business failure, across the social science domains, it is surprising that past studies have largely overlooked how extreme environmental shocks and 'black swan' events such as those caused by the coronavirus (COVID-19) pandemic and other global crises, can precipitate business failures. Drawing insights from the current literature on business failure and the unfolding event of COVID-19, we highlight the paradoxes posed by novel exogenous shocks (that is, shocks that transcend past experiences) and the implications for SMEs. The pandemic has accelerated the reconfiguration of the relationship between states and markets, increasing the divide between those with political connections and those without, and it may pose new legitimacy challenges for some players even as others seem less concerned by such matters, whilst experiential knowledge resources may be both an advantage and a burden.